MEMBANGUN TALENT MANAGEMENT UNTUK RETAIL X - Abel Tedjamulja (Business Administration Department - Universitas Katolik Parahyangan, 2020)
Empowerment of Human Resources through the correct management procedures to be one way in managing the existing Human Resources. Through the process of Talent Management as a way to identify to recruit, to develop, to retain and to maintain human resources can be managed properly and correctly. The type of research is descriptive research, which aims to describe how the state of the company today, then to conduct the process of identifying how a talent can be managed by the company. Data was collected from observations, interviews, surveys, and data record of directly from the company. Researcher began by looking for ways in which talent can be identified, how to process and how to recruit, develop, and retain employees in the company.The results describe the process of formulating and identifying the criteria of a talent, and how to recruit and select talents, as well as to propose talent development programs, and ways to retain talent. Specifically, this research takes cases for positions in the human resource and human capital divisions.The researcher gives suggestions for Talent Management implementation in the company, starting with the socialization of Talent Management and Talent Management model of Retail X. Furthermore, it is necessary to develop talent criteria formulation, for special competency competencies for positions outside the human resource and human capital divisions. Followed by an assessment and development program for selected talents.